RURAL CREDIT AND AGRICULTURE PERFORMANCE IN BRAZIL - Ana Cristina Maria; Amaral, Ana Maria Santana; Andrade, Juliana Mafra Salgado; Avelar, Jefferson Soares; Góes, Bruno César (Revista Brasileira de Engenharia de Biossistemas, 2021)
The creation of the National Rural Credit System (SNCR) in 1965 made it possible to modernize Brazilian agriculture with the acquisition of new machinery and agricultural implements, improving the productive system and productivity in the countryside, through financing with interest subsidized by the Federal Government, being considered the milestone for the establishment of the Green Revolution. Subsequently, new agricultural research institutes were created, such as the Brazilian Agricultural Research Corporation (Embrapa) in 1972, as well as assistance and rural extension companies, helping producers to obtain the best results in the field, increasing agricultural productivity and strengthening our agribusiness. This work aimed to carry out an analysis of the performance of Brazilian agriculture and its financing policies through the availability of subsidized rural credit for farmers.